Uji daya hambat minyak cengkeh terhadap bakteri Staphylococcus Aureus in Vitro - I Putu Wahyu Suryadinata; Dewa Made Sukrama; I Gusti Ayu Dyah Ambarawati (School of Dentistry Faculty of Medicine Udayana University, 2022)
Backround: Tooth extraction is a removal of a tooth from its socket inside the alveolar bone. The accumulation of bacteria inside the alveolar socket in the aftermath of a tooth extraction procedure may cause infection, for example, in the case involving Staphylococcus aureus bacteria. Once it occurs, a Staphylococcus aureus bacterial infection can then lead to fibrinolysis, which means the blood clotting process will not be taking place as normal. Clove oil, here, can be utilized as it contains a main active ingredient to act as an anti-bacterial agent. Objective: The purpose of this research was to find out clove oil’s effectiveness in preventing the Staphylococcus aureus bacterial accumulation, with a 40%, 60%, and 80% comparison. Methods: This research was conducted as a laboratory experimental research in vitro with Mueller Hinton Agar (MHA) acting as the breeding ground medium. The results showed that clove oil with 40% concentration had the average of 16 mm resistance zone against the Staphylococcus aureus bacteria, 60% concentration came up with the average of 17 mm, and 80% concentration lands the average of 17.80 mm. Results: The statistical test result showed a significant outcome (annova test = 0.001 with ρ<0,05). The method used was a comparison between the testing of the three clove oil concentration percentages as variables against the Staphylococcus aureus bacteria, which were clear zones each measured with a slide rule. Conclusion: From this research, it was discovered the 80% clove oil concentration had a stronger resistance power compared to its 40% or 60% precursor. Latar Belakang: Ekstraksi gigi adalah proses pencabutan gigi dari soket dalam tulang alveolar. Akumulasi bakteri pada soket alveolar pasca prosedur ekstraksi gigi dapat menimbulkan terjadinya berbagai macam infeksi salah satunya infeksi Staphylococcus aureus. Infeksi bakteri Staphylococcus aureus memiliki kemampuan untuk melisiskan fibrin sehingga proses pembekuan darah tidak dapat berlangsung secara normal. Minyak cengkeh adalah kandungan zat aktif utama yang dimana sifat minyak cengkeh sebagai anti bakteri. Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui perbandingan daya hambat minyak cengkeh terhadap akumulasi bakteri Staphylococcus aureus dengan konsentrasi 40%, 60%, 80%. Metode: Penelitian ini merupakan penelitian eksperimental laboratorium secara in vitro. Media biakan yang digunakan adalah Mueller Hinton Agar (MHA). Hasil penelitian memperlihatkan bahwa minyak cengkeh 40% memiliki rerata zona hambat 16 mm, 60% memiliki rerata 17 mm dan 80% memiliki rerata 17.80 mm dalam menghambat bakteri staphylococcus aureus. Hasil: Hasil uji statistik menunjukkan hasil yang signifikan (Uji annova = 0,001 dengan ρ<0,05). Metode yang digunakan adalah membandingkan diameter zona hambat dari minyak cengkeh bedasarkan variabel terhadap bakteri Staphylococcus aureus berupa zona bening yang diukur menggunakan jangka sorong. Simpulan: Kesimpulan yang bisa diperoleh dari penelitian ini adalah variable minyak cengkeh 80% memiliki daya hambat yang lebih besar dibandingkan dengan minyak cengkeh 40% dan 60%